Sistem Informasi Manajemen Kasir Berbasis Website Menggunakan Bahasa Pemrograman PHP dan Database MySQL - Sibarani, Fathiya Hasyifah (Universitas Methodist Indonesia, 2024)
The rapid advancement of information technology makes it easier and faster for humans to get information or assistance with their tasks. As long as the sales and payment processes at Hasiankupi Café are still carried out using a cash register, errors and problems continue to occur, especially in the process of preparing and distributing sales reports. This study intends to develop a web-based cashier management information system that can be utilized for the sales and payment processes at Hasiankupi Café. This web-based cashier management information system was developed using PHP and MySQL. Requirements Planning, Design Workshop, and Implementation are stages of the RAD system development method used. Use Case Diagrams, Sequence Diagrams, Activity Diagrams, and Class Diagrams are UML (Unified Modeling Language) diagrams used in designing management information systems. With this management information system, Hasiankupi Café employees can effectively and efficiently process food and beverage data, make payment transactions, and generate sales reports.